The prevalence and determinant factors of substance use among the youth in Ethiopia: A multilevel analysis of Ethiopian Demographic and Health Survey - Kassew, Tilahun; Tarekegn, Gebrekidan Ewnetu; Alamneh, Tesfa Sewunet; Kassa, Selam Fisiha; Liyew, Bikis; Terefe, Bewuketu (Frontiers in Psychiatry, 2023)
Background In Ethiopia, the youth are more exposed to substances such as alcohol, Khat, and tobacco than other populations. Despite the seriousness of the situation, low- and middle-income nations, particularly Ethiopia, have intervention gaps. Service providers must be made more aware of relevant evidence to combat these problems. This research focused on finding out how common substance abuse is among teenagers and the factors that influence it. Methods The 2016 Ethiopian Demographic and Health Survey data were used for secondary data analysis. This survey includes all young people aged 15 to 24 years. The total sample size was 10,594 people. Due to the hierarchical nature of the survey data, a multilevel logistic regression model was employed to uncover the individual- and community-level characteristics related to substances. Results In Ethiopia, the overall current prevalence of occasional or daily substance use 30 days prior to the survey was 46.74%. Of the participants, 36.34, 12.56, and 0.95% were drinking alcohol, chewing Khat, and smoking cigarettes/any tobacco products, respectively. Male sex, 20–24 years of age, exposure to media, having a job, and living in large central and metropolitan regions were the factors associated with the problem. Conclusion According to the 2016 EDHS, substance use among young people is widespread in Ethiopia. To lower the prevalence of substance use among youth, policymakers must increase the implementation of official rules, such as restricting alcohol, Khat, and tobacco product marketing to minors, prohibiting smoking in public places, and banning mass-media alcohol advertising. Specific interventions targeting at-risk populations, such as youth, are mainly required in prominent central and metropolitan locations.